통합사례관리 수행과 성과에 대한 공공과 민간 부문 전문가의 인식 비교 - 문영주; Moon Young-joo (한국거버넌스학회보, 2017)
이 연구는 통합사례관리 수행과 성과에서 공공과 민간 부문 전문가의 인식을 비교하는 데 연구의 목적이 있다. 연구목적을 달성하기 위해 부산·경남 지역의 공공과 민간 부문 사례관리 전문가를 대상으로 우편 설문조사를 실시하였다. 배포된 총 1,108부의 설문지 중 회수된 871부 가운데 성실히 응답한 858부를 최종 잠재평균분석한 결과는 다음과 같았다. 첫째, 대상자 발굴과 초기상담, 욕구·위기도 조사와 서비스 제공계획 등에서 공공 부문 전문가들은 민간 부문 전문가에 비해 사례관리 수행도를 더 높게 인식하는 것으로 나타났다. 둘째, 서비스의 중복 및 누락을 완화하고, 복지 사각지대를 줄여 주는 등의 통합성 면에서 민간 부문 전문가들은 공공 부문 전문가에 비해 사례관리 성과를 더 높게 인식하는 것으로 나타났다. 이러한 결과를 토대로 지역사회중심 민관협력 사례관리의 성공적 수행을 위한 시사점을 도출하였다. The purpose of this study was to compare experts from the public sector with those from the private sector in the perceptions of case management performance and outcomes. For that purpose, the investigator a mail survey with case management experts in the public and private sector in Busan and Gyeongnam Province on September 15~October 15, 2014. Total 1,108 questionnaires were distributed, and 871 were returned. After excluding the ones whose responses were insincere, the investigator used total 858 questionnaires in the final latent means analysis. The findings were as follows: First, the experts in the public sector had a higher perception of case management performance than their counterparts in the private sector in the aspects of identification of subjects, initial counseling, assessment survey of needs and risks, and service provision plans. Secondly, the experts in the private sector had a higher perception of case management outcomes than their counterparts in the public sector in the aspects of integration such as alleviating service overlapping and omission and reducing the blind spots of welfare. Based on those findings, the study provided implications for the successful performance of community-centered case management throughout public-private partnership.